P211 The changing epidemiology of TB disease 2016 – 2018 in a low incidence scottish health board: possible implications for TB elimination. (December 2018) - Warner, B; Wilkie, M; Ramsey, M; Chandler, D; Connell, D
Abstract : Introduction: TB incidence in the UK is falling, 1 and elimination may now be a realistic goal in line with the WHO End TB Strategy. In Scotland, numbers of cases are declining but anecdotally are becoming more complex, with implications for the approach to elimination in low-incidence environments. 2 NHS Tayside is a low-incidence health board (3.6 per 100, 000), with a socially-deprived urban centre, and a large rural population. Changes in TB epidemiology in Tayside were explored from 2016–2018, to assess if this anecdotal change in disease presentation was reflected in real-life practice. Method: Data for all cases in Tayside from January'16 to June'18 were obtained from Health Protection Scotland and local Enhanced Surveillance of Mycobacterial Infections and Cohort Review forms. Demographic and clinical details including country of birth, site of disease, and sputum smear status, were recorded. Results: Since 2016, the number of cases diagnosed in Tayside has risen from 3 in January-June 2016, to 12 in January-June 2018. In 2016 the majority of cases were extra-pulmonary (66%), however by 2018, 67% were pulmonary TB (figure 1). More recently, the proportion of UK born patients is increasing in Tayside (33% in January-June'16, 60% in January-June'18). The average time from symptom onset to treatment (in active pulmonary cases) was 117 days (compared to Key Performance Indicator of 2 months), and from diagnosis to treatment was 10.54 days (compared to KPI of 7 days). Conclusions: In the last six months, there appears to have been an increase in the proportion of patients who are UK born. In a low-incidence setting, the epidemiology of TB may be changing to one where cases are harder to manage and diagnose, but may represent more of a threat to ongoing transmission, given the rising proportion of pulmonary TB. Overall this may have implications for future service planning and TB transmission control strategies. References: Thomas HL, et al. Reduction in tuberculosis incidence in the UK from 2011 to 2015: A population-based study. Thorax2018;73:769–75. TB Framework for Scotland. Scottish TB network, on behalf of the Scottish Government October 2017.